I've got you under my skin: inflammatory response to elephant seal's lice. Issue 4 (15th July 2021) - Leonardi, M. S.; Krmpotic, C.; Barbeito, C.; Soto, F.; Loza, C. M.; Vera, R.; Negrete, J.
Abstract: Seals (Phocidae) undergo an annual cycle of moulting that implies hair regeneration, and in the case of southern elephant seals, it also involves the superficial strata of the epidermis. Therefore, surviving the moulting period is crucial for their obligate and permanent ectoparasites. Throughout evolutionary time, sucking lice (Echinophtiriidae) have developed morphological, behavioural and ecological adaptations to cope with the amphibious lifestyle of their hosts. Lepidophthirus macrorhini, the Southern elephant seal louse species, faces the additional challenge of surviving attached to the host during the moulting period. Since lice live on the skin, L . macrorhini has developed a unique survival strategy by piercing the skin of their host, thus keeping them protected from moulting. During fieldwork in Patagonia and Antarctica, skin samples with lice within were collected for histological analysis to assess whether these parasites caused damage to the host. Lice generate an inflammatory process in the host's dermis, and these lesions could alter the normal chemical and mechanical protective properties of the skin facilitating secondary infections. Further studies that analyse the potential pathogens in those skin lesions are necessary to properly assess the real impact of ectoparasites on their host health. Abstract : Lice usually live attached to the host's hair; however, Lepidophthirus macrorhini burrows into the seal's epidermis, thus avoiding being removed from the host during the moulting process. L . macrorhini probably use the robust first pair of legs to perforate the skin, and this perforation produced a cellular inflammatory response in the Southern elephant seal. These lesions could alter the normal chemical and mechanical protective properties of the skin and facilitate secondary fungal or bacterial infections